Hummus and homicide - Kashian, Tina (Kashian, Tina. Kebab Kitchen mystery., 2018)
Things are slow in the off-season in this Jersey Shore town, but Lucy doesn<U+2019>t mind. She doesn<U+2019>t even mind waitressing at the Kebab Kitchen. Her parents have put in a new hummus bar, with every flavor from lemon to roasted red pepper. It<U+2019>s fun to see their calico cat again, and to catch up with her old BFF, who<U+2019>s married to a cop now. She could do without Heather Banks, though. The Gucci-toting ex-cheerleader is still as nasty as she was back in high school . . . and unfortunately, she<U+2019>s just taken over as the local health inspector. Just minutes after eating at the Kebab Kitchen<U+2014>where she<U+2019>s tallied up a whole list of bogus violations<U+2014>she falls down dead in the street. Word on the grapevine is it<U+2019>s homicide, and Lucy<U+2019>s the number one suspect . . .